LEKI CYFROWE. PROBLEMATYKA PRAWNA - Więckowski, Zbigniew (Zeszyty Prawnicze, 2016)
Digital Medicines. Legal Aspects Summary The subject of this article is the legal examination of digital medicines, a new type of medicinal product. The basis for the author’s remarks is the procedure launched by the US FDA (US Federal Food and Drug Administration) to consider the application for the commercial admission of digital medicines. This is the first case of its kind. He analyses the legal status of medicines of this kind on the grounds of the applicable EU directives and Polish domestic law. His purpose is an analysis of the definition of medicinal products in the relevant EU directive and in the Polish provisions, and an assessment of whether and to what extent digital medicines comply with these conditions. The analysis also takes the current case law of the European Court of Justice into consideration. The last part of the article discusses the legal aspects of the reimbursement of digital medicines in the Polish public healthcare system, and the role they could play in shaping the new system of health services and reimbursement. The article concludes with observations on the legislation which would be required if digital medicines were to be introduced on the Polish market.